An innovative surgical technique for treating penile incarceration injury caused by heavy metallic ring - Baruah, S. J. (Medknow Publications, 2009)
Penile incarceration injury by heavy metallic ring is a rare genital injury. A man may place metal object for erotic or autoerotic purposes, for masturbation or increasing erection, and due to psychiatric disturbances are some of the reasons for a penile incarceration injury. The incarcerating injury results in reduced blood flow distal to the injury, leading to edema, ischemia, and sometimes gangrene. These injuries are divided into five grades and their treatment options are divided into four groups. Surgical techniques are reserved for the advanced grades (Grades IV and V). We describe an innovative surgical technique, which can be adopted in Grades II and III injuries.